Eco-ink Production from Waste Cooking Oil - Abdul Malek, Siti Nazirah; Syahronie, Nurul Fatihah; Roslan, Nurish Alysa Sofea; Sharip, Norazreen (Multidisciplinary Applied Research and Innovation, 2026)
The production of eco-ink creates an alternative to replace conventional inks that contain toxic materials. In this study, a binder, raw materials, natural pigment, and additives are combined to create an ink formulation from waste cooking oil. The characterization of the produced eco-ink was carried out through chemical characterization using UV-Vis spectroscopy and FTIR spectroscopy. Physical characterization involved tests such as viscosity, ink flow, pH, adhesion, and water resistance to determine the suitability of the eco-ink formulation for practical applications. The results demonstrated the broad absorption band in the range of 3000–3600 cm⁻¹ corresponds to the O-H stretching mode, which indicates that the -OH group is due to distilled water, ethanol or glycerin and is present in both the charcoal and butterfly pea flower (BPF) inks during FTIR analysis, and the viscosity was found to be 4-5 mPa.s. Since the ink flow time is shorter, it indicates a lower viscosity value. The pH values were 8.5 for charcoal ink and 8.6 for BPF ink. The adhesion for charcoal ink was 44.44% and for BPF was 100%. Water resistance was 74% for charcoal ink and 54% for BPF ink. Overall, these results indicated the potential for utilizing waste cooking oil as a viable raw material for new sustainable products like eco-ink.